Comparative evaluation of effectivity and safety of topical amorolfine and clotrimazole in the treatment of tinea corporis - Manasi Banerjee; Asim Kumar Ghosh; Sukumar Basak; Kapil Dev Das; Dwijendra Nath Gangopadhyay (Wolters Kluwer Medknow Publications, 2011)
Background: Tinea corporis is a common superficial dermatophytosis seen in tropical countries. Newer molecules are constantly being introduced for its treatment. Topical clotrimazole is in vogue as the treatment for this condition for a long time. Amorolfine is a comparatively recently introduced drug for topical use in this condition. Aims: To assess the effectivity and safety of amorolfine 0.25% cream in patients with tinea corporis, in comparison to clotrimazole 1% cream. Materials and Methods: Patients presenting with symptoms of tinea corporis were mycologically confirmed for the presence of fungal hyphae. They were randomly divided into two groups: one group received amorolfine and the other received clotrimazole. Treatment duration was for 4 weeks and study duration was for 8 weeks. Evaluation was carried out using the standard clinical parameters on day 1, day 14, day 28 and a follow-up on day 56. Adverse effects were also recorded. Data entry was done in Excel datasheet and analyzed with Epiinfo 2002. Chi-square test and t-test were used according to the type of data. Results: The patients of the two groups were matched at baseline in respect to their demographic profile. Analysis of collected data showed significant improvement in both the groups, suggesting that both the drugs were effective agents in tinea corporis infection. Between-groups comparison of mycological cure rate and clinical improvement showed no significant difference. Conclusion: Amorolfine 0.25% cream is found to be safe and effective, like clotrimazole, when used topically in tinea corporis.